PERANCANGAN APLIKASI BERBASIS ANDROID UNTUK PEMBELAJARAN TANGGA NADA DENGAN FRET GITAR - Alfred Putra; Lina Lina; Decky Sandra (LPPM Universitas Widya Dharma Pontianak, 2021)
In playing guitar not only the basics must be learned to be a reliable guitarist, of course the need for regular training and the right learning process. To achieve all that, of course there are difficulty factors faced by the giataris, one of which is in the learning process scales. The learning process scales that may not have additional features, will be able to complicate the development of the user's ability to use musical instruments such as guitars. By doing so, a learning application for scales with a guitar fret is designed that is expected to be easy to learn and can make a guitarist's development in playing guitar increase. In this study the research design used was a clausal (Experimental) research design, namely writing, testing and testing of teaching devices designed by presenting the tone literature using the Android operating system. The system analysis technique used is object-oriented techniques with modeling the Unified Modeling Language (UML), which has the role of helping to describe the procedures and data flow contained in the designed application. This study resulted in a learning application scales with an Android-based fret guitar as a tool in the learning process. Thus, users can use this application and learn it until their abilities increase as expected. This application also provides additional features that help in the learning process of the scales. The conclusion obtained by the author is to produce a learning application with fret guitar scales equipped with additional features such as guidelines for stem guitars, finger gymnastics and guitar techniques, and the learning process of scales with fret guitar can be applied to Android-based smartphones. The advice that the author can give is to add training features to playing a complete guitar and the addition of the form of guitar techniques. Keywords: scale, guitarist, android, learning